Penerapan Metode Certainty Factor Untuk Mendiagnosa Penyakit Erosi Pada Gigi : (Studi Kasus Klinik Sehati Bengkulu) - Reza Ardiansyah; Maryaningsih Maryaningsih; Jhoanne Fredricka (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Dental erosion is described as the loss of the enamel on the teeth. At first, people who experience tooth erosion will not feel that their teeth are experiencing tooth erosion, until when tooth erosion has reached the dentin. Tooth erosion that has reached the dentin is characterized by, among other things, a feeling of pain in the teeth. However, there are many people who are unfamiliar with dental erosion, so a system that can be accessed online is needed to help patients or the public to consult independently. This expert system is designed using the PHP Programming Language and MySQL Database and the method used is a certainty factor. The result of concultationtest with the system is able to determine the disease along with the intial treatment or treatment that be must be carried out based on the symstoms selected by the user.